Decomposing Distributional Changes in Pakistan - Inchauste, Gabriela; Winkler, Hernan (World Bank, Washington, DC, 2014)
This paper quantifies the contributions to distributional changes observed in Pakistan over the last decade. In contrast to methods that focus on aggregate summary statistics, the method adopted in this paper generates entire counterfactual distributions to account for the contributions of demographics, labor and non-labor incomes in explaining poverty reduction. The results show that the most important contributor was the growth in income. Moreover, this growth in income seems to be driven by returns to individual and household endowments, pointing to productivity increases as the driving force behind poverty reduction. Lower dependency ratios, transfers and remittances also contributed to poverty reduction, albeit to a smaller extent. Growth in productivity, particularly between 2001-02 and 2005-06 is consistent with estimates from aggregate accounts, which points to productivity growth led by movements of labor force away from agriculture and into industry and services. If the objective is to reach similar or accelerated poverty reduction and productivity growth going forward, increased investment in rural areas will be needed.